IMPLEMENTATION PRINCIPLE MUDHARABAH IN ISLAMIC BANKING IN INDONESIA - Muhamad Agung Dharmajaya (SEAN Institute, 2020)
Implementation principle mudharabah is the main pillar operational Islamic banking in Indonesia for push growth equitable economy. Research law normative This aim For analyze mechanism implementation contract mudharabah as well as mitigation strategy formulation risk in optimize financing for results. Research results show that mechanism mudharabah has integrated to in law positive through Constitution Number 21 of 2008 concerning Islamic Banking, DSN-MUI Fatwa, and OJK regulations, which include function fundraising (funding) and fund distribution (financing). However, optimization financing mudharabah Still face challenge big in the form of height risk asymmetry information and potential moral hazard from customers manager (mudharib ). As solution, Islamic banking implements mitigation strategies modern multidimensional risk. The strategy covering strengthening aspect juridical through tightening clause contracts (restrictive covenants) and bindings guarantee financing (rahn ). In addition, mitigation optimized past integration digital technologies such as system integrated Point of Sales cashier and account separate (segregated accounts) for monitor cash flow in real, scheme staged financing, and improvement HR competency becomes assessor financing specific industry. Research This conclude that strengthening management modern risk capable secure operational product for results without sacrifice sharia compliance.